The effect of the rand exchange rate on the JSE Top-40 stocks: An analysis for the practitioner - G. D.I. Barr; B. S. Kantor; C. G. Holdsworth (South African Journal of Business Management, 2007)
This paper investigates the relationship between the returns of the ALSI Top 40 companies and changes in the Rand-Dollar exchange rate. Each of the Top 40 companies was grouped, a priori, according to their global positioning vis-à-vis income and costs into four main categories; namely, Rand-hedge, Rand-leverage, Rand-play and Mixed. The expected reaction of each of the shares within these categories to movements in the exchange rate was in almost all cases confirmed by GARCH adjusted regression analysis over two separate periods, February 1999 to January 2002 and February 2002 to August 2005. Ranked t-statistics were then used to gauge the consistency of the risk-adjusted magnitude of share price changes with respect to changes in the exchange rate. This ranking allows investors to construct customised portfolios according to their expectation of future exchange rate movements and to more fully understand the exchange rate risk that their current portfolio may have.
Keywords: 650